Sunset of the sabertooth : the graphic novel - Osborne, Mary Pope; Laird, Jenny, 1969- (Mary Pope Osborne's magic tree house, 2024)
The magic tree house transports Jack and Annie on a mission to the Ice Age where they encounter Cro-Magnons, cave bears, sabertooth tigers, and woolly mammoths.